2017
DOI: 10.5897/ajb2017.15971
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen-fixing Bradyrhizobium elkanii significantly stimulates root development and pullout resistance of Acacia confusa

Abstract: Reforestation of native Acacia confusa Merr. on landslide areas in Taiwan is important for agroforestry and soil conservation. To ensure high survival and growth vigor, A. confusa seedlings must develop a strong root system. Inoculating of acacia with symbiotic nitrogen-fixing bacteria (NFB) may ameliorate the problems associated with soil nutrient deficiency on landslide sites. In this study, under plastic house condition, a NFB was isolated from the root nodules of native A. confusa and identified as Bradyrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The nitrogen-fixing tree species is vulnerable to numbers of diseases with heart rot, root rot and phyllode rust causing the most debilitating damages to the trees (Jung-Tai et al, 2017). Disease infection interfere the growth and development of the plant which consequently reduces quality and productivity.…”
Section: Pest and Diseasementioning
confidence: 99%
“…The nitrogen-fixing tree species is vulnerable to numbers of diseases with heart rot, root rot and phyllode rust causing the most debilitating damages to the trees (Jung-Tai et al, 2017). Disease infection interfere the growth and development of the plant which consequently reduces quality and productivity.…”
Section: Pest and Diseasementioning
confidence: 99%
“…Bradyrhizobium, a genus of Gram-positive that initially proposed as a group of slowgrowing, alkaline-producing root nodule nitrogen-xing bacteria [78]. B. elkanii isolated from the root nodules of Acacia confusa, exhibit the nitrogen-xing ability and can enhance the growth and root development of A. confuse [79]. Numerous studies revealed that endophytic bacteria can improve plant tness by enhancing nutrient mobilization, nitrogen xation, phosphate solubilization and conferring resistant against pathogens [27,80].…”
Section: Discussionmentioning
confidence: 99%
“…Innumerous researches show that symbiotic microorganisms can increase plant resistance to metal(oid)s toxicity by different ways, including changes in the metal uptake by plants [14][15]. Arbuscular mycorrhizal fungi (AMF) and nitrogen-fixing bacteria have a widespread occurrence in ecosystems and have been the most common plant associated beneficial microbes used as inoculants in remediation processes of metalcontaminated soils [11; 15-21].…”
Section: Introductionmentioning
confidence: 99%